HUBBLE PARAMETER MEASUREMENT CONSTRAINTS ON THE REDSHIFT OF THE DECELERATION-ACCELERATION TRANSITION, DYNAMICAL DARK ENERGY, AND SPACE CURVATURE - Farooq, O.; Madiyar, F. R.; Crandall, S.; Ratra, Bharat (My University, 2017)
We compile an updated list of 38 measurements of the Hubble parameter H(z) between redshifts 0.07 <= z <= 2.36 and use them to place constraints on model parameters of constant and time-varying dark energy cosmological models, both spatially flat and curved. We use five models to measure the redshift of the cosmological deceleration-acceleration transition, z(da), from these H(z) data. Within the error bars, the measured zda are insensitive to the model used, depending only on the value assumed for the Hubble constant H-0. The weighted mean of our measurements is z(da) = 0.72 +/- 0.05 (0.84 +/- 0.03) for H-0 = 68 +/- 2.8 (73.24 +/- 1.74) km s(-1) Mpc(-1) and should provide a reasonably model-independent estimate of this cosmological parameter. The H(z) data are consistent with the standard spatially flat.CDM cosmological model but do not rule out nonflat models or dynamical dark energy models.
Citation: Farooq, O., Madiyar, F. R., Crandall, S., & Ratra, B. (2017). HUBBLE PARAMETER MEASUREMENT CONSTRAINTS ON THE REDSHIFT OF THE DECELERATION-ACCELERATION TRANSITION, DYNAMICAL DARK ENERGY, AND SPACE CURVATURE. Astrophysical Journal, 835(1), 11. doi:10.3847/1538-4357/835/1/26
Keywords: Cosmological Parameters; Cosmology: Observations; Dark Energy; Luminous Red Galaxies; Variable Cosmological Constant; Baryon